A Comparative Tribo-Mechanical Behavior Analysis of Laser Cladded Nitronic 60 Coating Against Wrought Nitronic 60 Alloy. (September 2022) - Roy, Sougata; Sridharan, Niyanth; Gangopadhyay, Arup; Qu, Jun
Abstract: In this study the tribological and mechanical behavior of a laser cladded Nitronic 60 coating on maraging steel is compared to that of a wrought Nitronic 60 alloy. A multi-layer Nitronic 60 coating was deposited using laser directed energy deposition, and its microstructure, porosity, and microhardness were characterized. The microhardness of the coated region in the laser cladded Nitronic 60 varied between 270-300 HV whereas that for wrought form was 230 HV. Controlled tribological tests under motor oil lubricated conditions were conducted at both room and elevated temperatures. The laser cladded Nitronic coating exhibited poorer wear resistance at room temperature but higher wear resistance at elevated temperature as compared to the wrought Nitronic alloy. Severe plastic deformation and fracture was observed on the laser cladded coating after the wear tests at both temperatures. Wear mechanisms were investigated based on the morphological and compositional characterization of the wear tracks.